Contested Empire : Rethinking the Texas Revolution - Schlereth, Eric R. (Book collections on Project MUSE., 2015)
To a large degree, the story of Texas' secession from Mexico has been undertaken by scholars of the state. Early twentieth century historians of the revolutionary period, most notably Eugene Barker and William Binkley, characterized the conflict as a clash of two opposing cultures, yet their exclusive focus on the region served to reinforce popular notions of a unique Texas past. Disconnected from a broader historiography, scholars have been left to ponder the most arcane details of the revolutionary narrative-such as the circumstances of David Crockett's death and whether William Barret Travi.